Involvement of LDL and ox-LDL in Cancer Development and Its Therapeutical Potential - Deng, Chang-Feng; Zhu, Neng; Zhao, Tan-Jun; Li, Hong-Fang; Gu, Jia; Liao, Duan-Fang; Qin, Li (Frontiers in Oncology, 2022)
Lipid metabolism disorder is related to an increased risk of tumorigenesis and is involved in the rapid growth of cancer cells as well as the formation of metastatic lesions. Epidemiological studies have demonstrated that low-density lipoprotein (LDL) and oxidized low-density lipoprotein (ox-LDL) are closely associated with breast cancer, colorectal cancer, pancreatic cancer, and other malignancies, suggesting that LDL and ox-LDL play important roles during the occurrence and development of cancers. LDL can deliver cholesterol into cancer cells after binding to LDL receptor (LDLR). Activation of PI3K/Akt/mTOR signaling pathway induces transcription of the sterol regulatory element-binding proteins (SREBP), which subsequently promotes cholesterol uptake and synthesis to meet the demand of cancer cells. Ox-LDL binds to the lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) and cluster of differentiation 36 (CD36) to induce mutations, resulting in inflammation, cell proliferation, and metastasis of cancer. Classic lipid-lowering drugs, statins, have been shown to reduce LDL levels in certain types of cancer. As LDL and ox-LDL play complicated roles in cancers, the potential therapeutic effect of targeting lipid metabolism in cancer therapy warrants more investigation.